2020
DOI: 10.1093/femsle/fnaa020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diet on the microbiota of live-feed rotifers (Brachionus plicatilis) used in commercial fish larviculture

Abstract: Live-feed is indispensable to commercial fish larviculture. However, high bacterial loads in rotifers could pose a biosecurity risk. While this may be true, live-feed associated bacteria could also be beneficial to fish larvae through improved feed utilization or pathogen inhibition following host microbiota modification. The study objective was to elucidate the largely unexplored microbiota of rotifers propagated on five different diets through bacterial community profiling by 16S rRNA gene amplicon sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Compared to Daphnia , rotifer microbiome research is still in its infancy and the few existing studies focused on the commercially produced Brachionous plicatilis for fish farming (Ishino et al, 2012; Turgay et al, 2020). Our experimental evidence strongly suggests that the mechanism by which Lecane inermis acquires its microbiome greatly resembles that of Daphnia magna .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Daphnia , rotifer microbiome research is still in its infancy and the few existing studies focused on the commercially produced Brachionous plicatilis for fish farming (Ishino et al, 2012; Turgay et al, 2020). Our experimental evidence strongly suggests that the mechanism by which Lecane inermis acquires its microbiome greatly resembles that of Daphnia magna .…”
Section: Discussionmentioning
confidence: 99%
“…The NNV and Vibrio groups remained close to the control group, indicating that GIV might affect the enrichment and diversity of intestine communities. Previous studies revealed that the environment, dietary habits or disease also influence the structure of the intestinal bacteria in aquatic animals [18,22,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al (2017) suggested that the shift from one live feed product to another may be responsible for changes observed in the rearing water microbiome, which illustrates the possibility of outgrowth of bacteria from these sources. Live feeds have been associated with potential opportunistic pathogens and antibiotic-resistant bacteria (Mcintosh et al, 2008;Hurtado et al, 2020;Turgay et al, 2020); hence, it is crucial to understand the contribution of these microbes to the rearing water microbiome. Additionally, the magnitude and frequency of disturbances, such as nutrient shocks, have been shown to alter community assembly processes (i.e.…”
Section: Introductionmentioning
confidence: 99%